2014
DOI: 10.1002/hep.26783
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological inhibition of the chemokine C-C motif chemokine ligand 2 (monocyte chemoattractant protein 1) accelerates liver fibrosis regression by suppressing Ly-6C+macrophage infiltration in mice

Abstract: Macrophages constitute a major proinflammatory component during chronic liver diseases and are considered a key factor in promoting hepatic fibrosis. However, there is increasing evidence that distinct monocyte and macrophage subsets exert critical functions in regression from organ fibrosis as well. Experimental mouse models of fibrosis regression have identified “restorative” macrophages as Ly‐6C (Ly6C, Gr1) low‐expressing, monocyte‐derived cells. We investigated molecular pathways balancing proinflammatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
193
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(200 citation statements)
references
References 33 publications
7
193
0
Order By: Relevance
“…4,7,8 Work by a number of groups, including the study by Yang et al in this issue of Gastroenterology, has demonstrated that macrophages are crucial to the resolution of fibrosis. 4,7,[9][10][11] Indeed, the removal of the macrophage population at the onset of spontaneous fibrosis resolution in rodent models of liver injury prevents remodeling of fibrosis. Additionally, deletion of the macrophage population is associated with a critical drop in liver levels of key enzymes such as MMP13 and MMP12-identifying the macrophage as a crucial source of these enzymes in fibrosis resolution.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4,7,8 Work by a number of groups, including the study by Yang et al in this issue of Gastroenterology, has demonstrated that macrophages are crucial to the resolution of fibrosis. 4,7,[9][10][11] Indeed, the removal of the macrophage population at the onset of spontaneous fibrosis resolution in rodent models of liver injury prevents remodeling of fibrosis. Additionally, deletion of the macrophage population is associated with a critical drop in liver levels of key enzymes such as MMP13 and MMP12-identifying the macrophage as a crucial source of these enzymes in fibrosis resolution.…”
mentioning
confidence: 99%
“…Intriguingly, in the carbon tetrachloride-induced model of liver injury, the macrophages crucial for resolution are the same population that is recruited during fibrogenesis, and that contribute to fibrosis. 9,10 Associated with the onset of fibrosis resolution, this same macrophage population undergoes a phenotypic switch in situ, expressing markers that define a distinct phenotype and up-regulate the expression of matrix-degrading enzymes (and survival and proliferative signals for hepatocytes and hepatic progenitor cells) after ingestion of debris. 6,10 Against this background, the work by Yang et al 4 provides another crucial insight to the molecular regulators of fibrosis resolution.…”
mentioning
confidence: 99%
“…Modify leukocyte migration into tissues and consequent inflammation, tissue remodelling and fibrosis 94,95 .…”
Section: Competing Interests Statementmentioning
confidence: 99%
“…They concluded that M1 macrophages are predominantly present in fibrotic septa during resolution of fibrosis and releases various fibrolytic factors [11]. RNA-aptamer-based inhibitor of CCL2, termed mNOX-E36 reduces the infiltration of Ly6chi macrophage in fibrotic mouse models and favouring the shift of intrahepatic macrophage towards pro-resolution Ly6clo counterparts [12]. Cenicriviroc, the dual CCR2/CCR5 inhibitor in NASH shows promising results in Phase IIB clinical trial (NCT02217475) with decreased in inflammation and fibrosis [13].…”
Section: Change In Fibrogenic Microenvironmentmentioning
confidence: 99%